2019
DOI: 10.1016/j.qref.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Oil price and inflation in Algeria: A nonlinear ARDL approach

Abstract: This Article is brought to you for free and open access by the Journals and Magazines at Loyola eCommons. It has been accepted for inclusion in Topics in Middle Eastern and North African Economies by an authorized administrator of Loyola eCommons. For more information, please contact ecommons@luc.edu. This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 3.0 License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 33 publications
(40 reference statements)
10
66
1
1
Order By: Relevance
“…In this case, the tests revealed the existence of stability in the model because the coefficients' estimated model laid within 5% significant line for the CUSUM and CUSUM square tests. This results were similar with findings from Lacheheb (2016). Table 5 illustrates the results of the turning point obtained from NARDL estimation results in Table 4.…”
Section: Long-run Equation In Asean-5 Countriessupporting
confidence: 88%
“…In this case, the tests revealed the existence of stability in the model because the coefficients' estimated model laid within 5% significant line for the CUSUM and CUSUM square tests. This results were similar with findings from Lacheheb (2016). Table 5 illustrates the results of the turning point obtained from NARDL estimation results in Table 4.…”
Section: Long-run Equation In Asean-5 Countriessupporting
confidence: 88%
“…Despite these arguments, many studies still reported significant effects of oil price changes on economy especially on domestic price/ inflation. These studies include Kargi (2014), Abounoori, Nazarian, and Amiri (2014), Jiranyakul (2016) and Lacheheb and Sirag (2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using an augmented Phillips curve framework, LeBlacc, Chinn (2004) found that a 10% increase in oil price increases the price level by 0.1 to 0.8% in the US and European Union (EU). Employing a nonlinear autoregressive distributed lag (NARDL), a study on the Algerian economy shows that oil price increase causes inflation while oil price decrease seems unrelated to inflation both in the long and short run periods (Lacheheb, Siraj 2016). Hooker (2002) stated that oil prices significantly affect inflation in his study in two different time periods.…”
Section: The Resource Cursementioning
confidence: 99%